The Role of Self-Esteem and Self-Efficacy in Moderating the Effect of Workplace Stress on Depression, Anxiety and Stress. (20th June 2014) - Thompson, Jason; Gomez, Rapson
Abstract : Seventy-eight employees (32 males, 46 females) took part in a study to test the hypothesis that the core self-evaluation components of self-esteem and self-efficacy moderate the relationship between workplace stressors (role conflict and role-ambiguity) and strain (depression, anxiety, and tension-stress). Results supported our hypotheses in that self-efficacy moderated the relationship between role ambiguity and depression and between performance role ambiguity and stress, while self-esteem moderated the relationship between role ambiguity and anxiety, between performance role ambiguity and anxiety, and between performance role ambiguity and stress. These findings reinforce the importance of considering role stress variables in relation to the context of an interactive person/environment fit model and provide further insight into the nature of the stress process itself. Furthermore, these results indicate that the function of self-esteem and self-efficacy in the stress process is not identical. Implications for the conceptualisation of the transactional model of stress are discussed.